2020
DOI: 10.1111/ddi.13053
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid and strong population genetic differentiation and genomic signatures of climatic adaptation in an invasive mealybug

Abstract: Aim A growing number of studies suggest that adaptation of invasive species plays key roles in their successful establishment in novel environments. However, adaptation of invasive species to climatic conditions remains poorly characterized. This study aimed to understand the population genetic structure produced by the cotton mealybug Phenacoccus solenopsis invasion and to identify preliminary signals of selection during its range expansion. Location China. Methods We examined genetic structure of 11 populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…Gene flow within a native range may also promote the invasiveness of species by producing admixture from different sources that could facilitate the evolution of novel phenotypes (van Boheemen et al, 2017). Nevertheless, some successful invaders can establish their populations in newly colonized areas following a single introduction (Cao et al, 2016; Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Gene flow within a native range may also promote the invasiveness of species by producing admixture from different sources that could facilitate the evolution of novel phenotypes (van Boheemen et al, 2017). Nevertheless, some successful invaders can establish their populations in newly colonized areas following a single introduction (Cao et al, 2016; Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As such, understanding the demographic and evolutionary origins of introduced species is important if we are to understand evolution and biodiversity in the Anthropocene. Research has shown how introduced populations can rapidly differentiate from populations in their native range and adapt to their introduced range (Dupuis et al, 2018;Koch et al, 2020;Ma et al, 2020;Stuart et al, 2021;Zayed & Whitfield, 2008);…”
Section: Discussionmentioning
confidence: 99%
“…As such, understanding the demographic and evolutionary origins of introduced species is important if we are to understand evolution and biodiversity in the Anthropocene. Research has shown how introduced populations can rapidly differentiate from populations in their native range and adapt to their introduced range (Dupuis et al, 2018 ; Koch et al, 2020 ; Ma et al, 2020 ; Stuart et al, 2021 ; Zayed & Whitfield, 2008 ); however, the origin of that adaptive variation is seldom known (however, see Calfee et al, 2020 ). In this manuscript, we leveraged genome sequences to provide evidence that introduced populations of Z .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsatellites, also known as simple sequence repeats (SSRs), are 1–6 bp motifs present in both coding and non-coding regions of eukaryotic and prokaryotic genomes that have become the primary source of genetic markers for population analysis in insects due to their high levels of polymorphism [ 13 ]. It is well established that SSRs have high rates of mutation and thus have implications for genome organization and genetic variation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%